Total synthesis of (+)-petromyroxol, (-)-iso-petromyroxol, and possible diastereomers - Mullapudi, Venkannababu; Ahmad, Iram; Senapati, Sibadatta; Ramana, V, Chepuri (ACS Omega, 2020)
The total synthesis of (+)-petromyroxol (1) and its seven diastereomers including the ()-tso-petromyroxol (2) is described. The employed strategy involves the use of easily available CS-epimeric epoxides 5 and 5' and nonselective anomeric C1-allylation, proceeding with or without inversion at C2 thereby giving the possibility of synthesizing all possible diastereomers. Extensive two-dimensional (2D) NMR analyses of all eight diastereomers have been carried out to assign the chemical shifts of the central carbons land the corresponding attached hydrogens and to learn how the C/H-chemical shifts of the tetrahydrofuran ring were influenced by the adjacent centers.